2022
DOI: 10.1038/s41467-021-27891-4
|View full text |Cite
|
Sign up to set email alerts
|

Cosmogenic radionuclides reveal an extreme solar particle storm near a solar minimum 9125 years BP

Abstract: During solar storms, the Sun expels large amounts of energetic particles (SEP) that can react with the Earth’s atmospheric constituents and produce cosmogenic radionuclides such as 14C, 10Be and 36Cl. Here we present 10Be and 36Cl data measured in ice cores from Greenland and Antarctica. The data consistently show one of the largest 10Be and 36Cl production peaks detected so far, most likely produced by an extreme SEP event that hit Earth 9125 years BP (before present, i.e., before 1950 CE), i.e., 7176 BCE. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 65 publications
6
58
0
Order By: Relevance
“…69 on 20 January (* 1.2) (Asvestari et al 2017a, b;Cliver et al 2020a, b;Usoskin et al 2020a, b; International GLE Database (https://gle.oulu.fi)). The recently reported 7176 BC event has also been confirmed to be a hard spectrum event (Brehm et al 2021(Brehm et al , 2022Paleari et al 2022). These hard spectra imply that while the high-energy SEP fluence of the 774 AD event was extreme, the fluence in the 10-30 MeV range was not enhanced commensurately.…”
Section: Energy Spectra Of Cosmogenic-based Sep Eventsmentioning
confidence: 78%
See 2 more Smart Citations
“…69 on 20 January (* 1.2) (Asvestari et al 2017a, b;Cliver et al 2020a, b;Usoskin et al 2020a, b; International GLE Database (https://gle.oulu.fi)). The recently reported 7176 BC event has also been confirmed to be a hard spectrum event (Brehm et al 2021(Brehm et al , 2022Paleari et al 2022). These hard spectra imply that while the high-energy SEP fluence of the 774 AD event was extreme, the fluence in the 10-30 MeV range was not enhanced commensurately.…”
Section: Energy Spectra Of Cosmogenic-based Sep Eventsmentioning
confidence: 78%
“…• The fact that no events with F 30 [ 10 11 (cm 2 year) -1 have been found, and are unlikely to be found, over the Holocene, poses an upper 90% confidence interval limit P([ 10 11 (cm 2 year) -1 ) B 1.9 9 10 -4 year -1 . • Five historical events (7176 BC, 5259 BC, 660 BC, 774 AD, 993 AD) with F 30 [ 5 9 10 10 (cm 2 year) -1 (Mekhaldi et al 2015;O'Hare et al 2019;Paleari et al 2022;Brehm et al 2022) have been so far discovered and confirmed during the Holocene, but additional similar events may be found as the search continues. Accordingly, a lower limit of P([ 5 9 10 10 (cm 2 year) -1 )-C 1.2 9 10 -4 year -1 has been set.…”
Section: A Composite > 30 Mev Cumulative Occurrence Frequency Distrib...mentioning
confidence: 99%
See 1 more Smart Citation
“…after the end of the ring formation period in Ireland, the Alps and the Russian north, but before the end of tree ring formation in California, this would result in increased 14 C content of the 5260 BCE bristlecone pine tree ring, but not in the other chronologies. However, this cannot be argued on the basis of published information on the end of today’s growing seasons (Bristlecone pine—late August 43 , 44 , Alpine larch—October 45 , Irish oak – October 46 , Siberian larch-late August). Furthermore, the fact that the event occurred during the Holocene climatic optimum, which was characterized by a weaker latitudinal temperature gradient 47 , may mean that more synchronous growing seasons would be more likely.…”
Section: Discussionmentioning
confidence: 97%
“…Polar ice cores, which are regarded as extremely valuable climate archives, have typically been dated with a precision of about 10 years within the Holocene 29 and even less in the transition to the glacial period 42 . The absolutely dated 14 C events in tree-rings can now be used to synchronize the ice core chronologies via cosmogenic 10 Be and 36 Cl resulting in a precision of about 1-2 years limited by several factors such as weather noise, sampling, and radionuclide transfer times to the ice core 43 . As a result, chronologies that so far were synchronized with absolutely dated tree-ring records using the low resolution structure of existing 14 C or 10 Be records 29 can now be placed within 1-2 years or about 10 times more precisely around these events using the abrupt change in radionuclide concentrations caused by SEP events.…”
Section: Discussionmentioning
confidence: 99%